Assessment of Carbon Capture and Storage in Plantation and Garden Agroecosystems in Tuntang Hulu Sub-Watershed - Rosita Mustikasari; Bistok Hasiholan Simanjuntak (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Agroecosystems such as gardens and plantations play a crucial role in climate change mitigation through carbon capture and storage (CCS). This study aimed to analyze the carbon storage potential of these two agroecosystem types in the Tuntang Sub-Watershed and to examine the factors influencing it. A quantitative-descriptive approach was employed, involving biomass measurement both above and below round, along with analyses of soil physical and chemical properties at 41 sampling points. Results showed that the average CCS capacity in plantation areas reached 380.51 tons/ha, slightly higher than that of gardens at 333.30 tons/ha, although the difference was not statistically significant. Contributing factors to carbon storage capacity included vegetation type, soil pH, soil texture, and bulk density. Plantations were dominated by perennial woody crops producing higher biomass, whereas gardens were more commonly planted with annual crops. Therefore, well-planned vegetation management, particularly mixed agroforestry systems, has the potential to enhance CCS efficiency. These findings serve as an important foundation for planning sustainable agroecosystem management as a strategy for climate change adaptation and mitigation.